Structures of lithium salts of substituted 1-phenylpropynes: 13C NMR and MNDO study - Dem'yanov, Piotr I.; Styrkov, Igor M.; Krut'ko, Dmitry P.; Vener, Michail V.; Petrosyan, Valery S. (Journal of organometallic chemistry, 1992)
13C NMR spectroscopy has been used to study the structure of ambident carbanions in contact (CIP) and solvent-separated (SSIP) ion pairs of lithium salts of substituted 1-phenylpropynes. It was shown that the structures of carbanions in SSIP are close to the propargylic type, whereas, with the decrease in delocalizing ability of substituents at the propargylic centre, their structure shifts to the allenylic type, in fair agreement with theoretical predictions by the MNDO semi-empirical method. In CIP, the structures of carbanions are progressively changed from near-to-propargylic to allenylic with decrease of delocalizing ability of the substituents.